Long-Term Effects of Mind-Body Exercises on the Physical Fitness and Quality of Life of Individuals With Substance Use Disorder—A Randomized Trial - Zhu, Dong; Jiang, Mei; Xu, Ding; Schöllhorn, Wolfgang I. (Frontiers in Psychiatry, 2020)
Background: Mind-body exercises (MBE) are sequences of low to medium-intensity activities that benefit healthy performers physically and mentally. In contrast to the unmodified application of traditional tai chi, qi gong, or yoga in the healthy population, MBEs are typically tailored for individuals with substance abuse disorder (SUD). Despite numerous applications in practice, the detailed effects of tailor-made MBEs for SUD are unclear. Objectives: This study aimed to analyze and compare changes in the physical fitness and quality of life of individuals with SUD that underwent conventional or tailor-made MBEs. Methods: A total of 100 subjects obtained from the Shanghai Mandatory Detoxification and Rehabilitation Center with SUD were randomly assigned into two groups. The subjects in the experimental group (n = 50) practiced tailored MBE for 60 min a day, five times a week, for 3 months. The subjects (n = 50) in the control group were treated with conventional rehabilitation exercises with the same intervention protocol. The outcomes of fitness and quality of life for drug addiction were measured at the beginning and after 3 and 6 months by a questionnaire (QOL-DA). A two-way repeated measure analysis of variance was applied to compare the difference of treatments in the two groups. Results: Statistically significant differences for the experimental group were found in systolic (p < 0.01, η2 = 0.124) and diastolic blood pressure (p < 0.01, η2 = 0.097), pulse (p < 0.01, η2 = 0.086), vital capacity (p < 0.05, η2 = 0.036), flexibility (p < 0.01, η2 = 0.143), and aerobic endurance (p < 0.01, η2 = 0.165). Results of the QOL-DA showed statistically significant differences between the experimental and control groups in total score (p < 0.01, η2 = 0.158) with greater effects on the former. Conclusions: This study provided evidence that tailored MBE could lead to remarkable effects with regard to blood pressure, vital capacity, flexibility, and aerobic endurance in comparison with conventional rehabilitation methods. Clinical Trial Registration: ChiCTR-IPR-14005343.